Implicit Taxes Amid Race to the Bottom in a Global Tax Game - Igor Semenenko; Junwook Yoo; Parporn Akathaporn (Journal of Accounting, Business and Management (JABM), 2020)
Growing tax competition among national governments in the presence of capital mobility distorts equilibrium in the international corporate tax market. This paper is related to the literature that examines impact of international tax policies on corporate accounting statements. Employing international firm-level data, this study revisits the race-to-the-bottom hypothesis and documents that tax exemptions lowering effective tax rates relative to statutory rates increase pre-tax returns. This finding directly contradicts the implicit tax hypothesis documented by Wilkie (1992), who provided empirical evidence on inverse relationship between pre-tax return and tax subsidy. We also find evidences that relative importance of permanent versus timing component depends on the geography and that decline in corporate tax rates reduces impact of tax subsidies on profitability. Our findings suggest that tax subsidies play a different role than in 1968-1985, which was examined by Wilkie (1992). These results are consistent with the race-to-the-bottom hypothesis and income shifting explanation